GEREJA MEMPERHATIKAN ORANG MISKIN SEBAGAI REVELASI DAN KONTEMPLASI SUBSTANSI EVANGELIUM: REFLEKSI KRISTIS ATAS DOKUMEN EVANGELII GAUDIUM - Heribertus Susanto (Institut Teknologi Sepuluh Nopember, 2015)
The Church itself is a sacrament or a mystery. Her life and development are inspired by the Holy Spirit. The Church herself has a fundamental mission to proclaim evangelization and the kingdom of God. God, who reigns, has a preferential option for the poor. God has a special heart for the poor as well. It is great, so God, which incarnate in Jesus - The Gospel - Evangelium – lives a reality in the way of the poor. The Church is constantly called to have attention to the poor and account them. In this way, the Church encounters her Lord, whom reveals Himself within the poor. The poor, then, became lord and master. For they have taught the Church find the quality of the values. It comes from God which signed by love, solidarity and compassion. Serving and having attention to the poor are in fact a spiritual direction to contemplate Jesus the Lord. There, the Church and the world at large, eventually, will find a redemption and transformation of the living, and find the joy of the Gospel as well.